Andrographis paniculata ethanolic extract affects the spleen’s histopathology of Salmonella-infected mice - Isnaeni, Purnaning Dhian; Auza, Fuji Astuty; Napirah, Astriana; Prasanjaya, Putu Nara Kusuma; Kimestri, Asma Bio; Amri, Indah Amalia; Widianingrum, Desy Cahya; Fajrin, Eistifani; Khasanah, Himmatul (Jurnal Ilmiah Peternakan Halu Oleo, 2026)
Andrographis paniculata, AP, is one of the herbs that are widely utilised as an alternative medicine for its active ingredients, especially andrographolide, which acts as an anti-inflammatory, antibiotic, and immunomodulator. Andrographolide’s use as an immunomodulator in many animal models has been recorded, but the effect on the spleen of mice infected by bacteria, particularly Salmonella sp. has yet to be done so far. Forty mice were grouped into five different treatments in a completely randomised design: control negative (uninfected, untreated mice), control positive (infected, untreated mice), AP1 (infected, 200mg/kg BW AP), AP2 (infected, 300mg/kg BW AP), and AP3 (infected, 400mg/kg AP). The collected data was analysed to determine the effect of AP extract on mice’s spleen. The results showed that AP extract maintain the tissue damage of the spleen in Salmonella-infected mice to be minimum, as compared to the control positive. AP3 treatment has not been proved to repair the damaged tissue of spleen infected with Salmonella sp.